Genetic variation in leptin and leptin receptor genes as a risk factor for idiopathic male infertility. (3rd November 2016) - Hodžić, A.; Ristanović, M.; Zorn, B.; Tulić, C.; Maver, A.; Novaković, I.; Plaseska‐Karanfilska, D.; Peterlin, B.
Summary: The aim of this study was to examine whether there is an association among genetic variability in leptin ( LEP ) and leptin receptor ( LEPR ) genes and male infertility. We performed a case–control study and were searching for an association between polymorphisms of LEP and LEPR genes and male infertility. The study group consisted of 317 patients with idiopathic infertility and a control group of 241 fertile men from Slovenia. Four single nucleotide polymorphisms (SNPs) in LEP gene and four single nucleotide polymorphisms (SNPs) in LEPR gene were chosen and genotyped. Statistically significant SNP was further validated in additional 255 infertile patients and 168 controls from Serbia and Macedonia. In the Slovenian population, we found a statistically significant difference in genotype distribution for rs10244329 polymorphism in LEP gene (recessive genotype model, p value = 0.048). The trend toward statistically significant difference in genotype distribution for rs10244329 polymorphism was confirmed in the Serbian and Macedonian populations ( p value = 0.07). Our data suggest that genetic variability in the LEP gene might be associated with male infertility warranting further confirmation and mechanistic investigations.